Methods of research on teaching the English language arts : (Erlbaum Associates, 2005)
A concise format of the research methodology section of the "Handbook of Research on Teaching the English Language Arts", Second Edition. Designed to give K-12 teachers an understanding of the basic categories and functions of research in teaching, is followed by chapters addressing teacher professionalism and the rise of "multiple literacies".